Ameliorative Effects of Magnesium and Copper Sulphates on Blood glucose and Serum Electrolytes Levels in Fructose-induced Diabetic Wistar Rats - Tanko Y, Ismail A.S,Mohammed K. A,Eze E.D, Jimoh A,Sada N. M,Muhammad A and Mohammed A (Journal of Applied Pharmaceutical Science, 2013)
The aim of this study is to evaluate the effects of magnesium and copper sulphates on blood glucose and serum electrolytes levels in fructose-induced diabetic Wistar rats. Diabetes was induced by administration of 20% (20g/100ml) of fructose dissolved in distilled water and administered to the animals for a period of six (6). After which the animals were randomly assigned into 4 groups of 6 rats each. Group I served as diabetic control and were administered distilled water, Group II were administered Magnesium sulphate (250 mg/kg b w), Group III were administered Copper sulphate (250 mg/kg b w) and Group IV administered Metformin (250 mg/kg b w). All treatments were given orally for a period of seven days. The results obtained showed a statistically significant decrease (p
Keywords: Diabetes, magnesium sulphate, copper sulphate, blood